Counseling on The Importance of The Diction of “Side Dishes Amis-Amis” for Pregnant, Breastfeeding Women and Toddler for Preventing Bad Nutrition and Stunting in Kalisat Village, Jember District, East Java - Asrumi; Asri Sundari; Anastasia Erna R.S.; I.G. Krisnadi; Imam Basuki; Hanny Rasni; Sofia (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2024)
Jember Regency ranks 8th in East Java and 11th in Indonesia for cases of malnutrition and stunting in infants. Kalisat District is among the top 5 for stunted babies in Jember. The root of the problem is not only the local economy but also the public's understanding of the term